A comprehensive test set of epoxidation rate constants for iron(iv)–oxo porphyrin cation radical complexes. Issue 2 (19th December 2014) - Sainna, Mala A.; Kumar, Suresh; Kumar, Devesh; Fornarini, Simonetta; Crestoni, Maria Elisa; de Visser, Sam P.
Abstract : Trends in oxygen atom transfer to Compound I of the P450 models with an extensive test set have been studied and show a preferred regioselectivity of epoxidation over hydroxylation in the gas-phase for the first time. Abstract : Cytochrome P450 enzymes are heme based monoxygenases that catalyse a range of oxygen atom transfer reactions with various substrates, including aliphatic and aromatic hydroxylation as well as epoxidation reactions. The active species is short-lived and difficult to trap and characterize experimentally, moreover, it reacts in a regioselective manner with substrates leading to aliphatic hydroxylation and epoxidation products, but the origin of this regioselectivity is poorly understood. We have synthesized a model complex and studied it with low-pressure Fourier transform-ion cyclotron resonance (FT-ICR) mass spectrometry (MS). A novel approach was devised using the reaction of [Fe III (TPFPP)] + (TPFPP = meso -tetrakis(pentafluorophenyl)porphinato dianion) with iodosylbenzene as a terminal oxidant which leads to the production of ions corresponding to [Fe IV (O)(TPFPP + ˙)] + . This species was isolated in the gas-phase and studied in its reactivity with a variety of olefins. Product patterns and rate constants under Ideal Gas conditions were determined by FT-ICR MS. All substrates react with [Fe IV (O)(TPFPP + ˙)] + by a more or less efficient oxygen atom transfer process. In addition, substrates with low ionization energies react by a charge-transfer channel, which enabled us to determine the electron affinity of [Fe IV (O)(TPFPP + ˙)] + for the first time. Interestingly, no hydrogen atom abstraction pathways are observed for the reaction of [Fe IV (O)(TPFPP + ˙)] + with prototypical olefins such as propene, cyclohexene and cyclohexadiene and also no kinetic isotope effect in the reaction rate is found, which suggests that the competition between epoxidation and hydroxylation – in the gas-phase – is in favour of substrate epoxidation. This notion further implies that P450 enzymes will need to adapt their substrate binding pocket, in order to enable favourable aliphatic hydroxylation over double bond epoxidation pathways. The MS studies yield a large test-set of experimental reaction rates of iron(iv )–oxo porphyrin cation radical complexes, so far unprecedented in the gas-phase, providing a benchmark for calibration studies using computational techniques. Preliminary computational results presented here confirm the observed trends excellently and rationalize the reactivities within the framework of thermochemical considerations and valence bond schemes.